2017
DOI: 10.12738/estp.2017.3.0090
|View full text |Cite
|
Sign up to set email alerts
|

Investigating EFL Coursebook Research in Turkey: Trends in Graduate Theses of the 2001-2013 Period

Abstract: The transformation of coursebook publishing into an industrial giant has brought about variety, choice, and difficulty of decision making. As coursebook selection profoundly influences the quality of foreign language instruction in Turkey, it is essential to investigate what kind of instruments are used, which method is followed, what criteria are sought and how relevant parties are affected by its results. Therefore, 54 graduate theses evaluating EFL coursebooks in the 2001-2013 period were taken from the CoH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Other than the aforementioned ones, the least used methods were the ones that the researchers applied for introducing the technologies they developed. Similar to this study, there are some other studies in the relevant literature which found that the majority of the studies applied quantitative method most (Şimşek et al, 2008;Gülbahar and Alper, 2009;Şimşek et al, 2009;Göktaş et al, 2012;Kiliç-Çakmak et al, 2013;Kılıç Çakmak et al 2015). It can be concluded from these findings that quantitative methods have been applied quite sufficiently in educational technologies, and researchers should give weight to qualitative, mixed and literature review methods as well.…”
supporting
confidence: 82%
“…Other than the aforementioned ones, the least used methods were the ones that the researchers applied for introducing the technologies they developed. Similar to this study, there are some other studies in the relevant literature which found that the majority of the studies applied quantitative method most (Şimşek et al, 2008;Gülbahar and Alper, 2009;Şimşek et al, 2009;Göktaş et al, 2012;Kiliç-Çakmak et al, 2013;Kılıç Çakmak et al 2015). It can be concluded from these findings that quantitative methods have been applied quite sufficiently in educational technologies, and researchers should give weight to qualitative, mixed and literature review methods as well.…”
supporting
confidence: 82%
“…The activities do not motivate students for autonomous responses; instead, they encourage students to work in pairs or groups. Şimşek and Dündar (2017) note that teachers should study their content after choosing a textbook and make preparations accordingly. An adaptation process generally follows this.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the theses conducted on coursebook use in Turkey, Şimşek and Dündar (2017) investigated how graduate theses tacked the issue of coursebook use and evaluation in Turkey between 2001 and 2013. The authors analyzed 54 graduate theses, and in the light of the findings, it was determined that the studies mostly focused on the evaluation of the coursebooks used in the schools and obtained teachers' and student views on varied coursebooks through similar questionnaires and checklists.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This activity seemed to enable them to consider the general teaching principles as well as the language teaching practices. As indicated by Şimşek and Dündar (2017), it is of vital importance that teachers be trained in the evaluation and adaptation strategies. Despite the promising benefits of designing supplementary activities, some concerns were also voiced by the participants such as the amount of time needed.…”
Section: Research Questionmentioning
confidence: 99%